Design and Implementation of Web-Based Islamic Education Management Information System to Improve the Efficiency and Effectiveness - Dandi Handika Bayu; Luqi Darmawan; Muhammad Syuhada' Subir (STAI MA'ARIF MAGETAN, INDONESIA, 2026)
Digital transformation in the management of Islamic educational institutions is a strategic need in the modern era that demands efficiency, transparency, and speed in data management. This study aims to examine the implementation of the web-based Islamic Education Management Information System (SIMPI) at MA Ma'arif 03 Sidomulyo and its impact on service efficiency and institutional governance. This research uses a field qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study show that the implementation of SIMPI has had a positive impact in accelerating the administrative process, improving data accuracy, and facilitating access to information, especially in the management of student data, academic grades, and finances. However, the system has not been implemented evenly. Some units such as teacher attendance, letter archiving, and teacher performance evaluation are still running manually. The main challenges faced are the low digital literacy of users, the lack of continuous technical training, the limited supporting infrastructure, and the lack of comprehensive system integration between units. This research recommends strengthening human resources, improving infrastructure, and institutional commitment so that management digitalization can run optimally and sustainably.